The Effect of Motivation to Participate in Sport on Prosocial and Antisocial Behaviors in Individuals with Physical Disabilities - Elif Top; Mustafa Akil (Tehran University of Medical Sciences, 2021)
Background: This cross sectional study was conducted to analyse the level of motivation and prosocial as well as antisocial behaviors of the individuals with physical disabilities who do sports, to evaluate whether their motivational states were related with prosocial and antisocial behaviors, and to determine if the type of disability affect their motivation or prosocial and antisocial behaviors. Method: The research was conducted on 688 individuals who do sports and have physical disabilities in various regions of Turkey in 2020. Motivation Scale for Sports Participation of People with Disabilities (MSSPPD), Prosocial and Antisocial Behavior in Sport Scale (PABSS) were used as data collection tools in this research. Results: Motivation to participate in sports level of the individuals with physical disabilities was quite high. Their prosocial behavior towards their teammates and opponents was high, while their antisocial behavior towards teammates and opponent team players was low. When subjects' motivations were examined according to the type of disability, motivation levels of individuals with orthopedic and visual disabilities were higher than those of individuals with hearing disabilities. Conclusion: As a result, individuals with disabilities need strong motivation to participate in sport programs and this improves them behaviourally. As their motivation for participation in sport increased, their prosocial behaviors were positively affected, and their antisocial behaviors decrease.